PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL KELAS IV SD - Angga Triska; Tio Gusti Satria; Novianti Mandasari (Primary Education Journal Silampari (PEJS), 2022)
This study aims to determine student learning outcomes after the implementation of the cooperative learning model in Social Science subjects for Class IV SD Negeri 18 Lubuklinggau City is significantly complete. The experimental design used was in the form of a pre-test-post-test group. The pre-test-post-test group, namely the pre-test and post-test were given to the experimental class. The population in this study were all fourth grade students of SD Negeri Lubuk Kemang with a sample of 20 students. The data collection technique used is the test, the analysis technique uses the t test. The results of the study concluded that the Cooperative Learning model could complete the learning outcomes of Class IV students at SD Negeri 18 Lubuklinggau in social studies learning. After applying the Cooperative Learning model, students are more interested and interested in social studies learning. This can be seen from the increase in learning outcomes carried out through pretest and posttest activities. In the pretest the overall average score of 69.29 students was declared incomplete while in the posttest the overall average value of the students increased to 85.18 and was declared complete with tcount = 4.27 < ttable = 1.32, then Ha was accepted as mean the average student learning outcomes after the implementation of cooperative learning is significantly complete. Keywords: Cooperative Learning, Model, Social Sciences, Elementary School